Metal Oxides - Grilli, Maria Luisa (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue contains ten research papers, three of which review papers. It is a miscellaneous composition encompassing several applications where metal oxides play a key role. Some papers also give insights into novel synthesis methods and processes aiming to reduce negative environmental impacts and increase materials and process efficiency, thus also covering a broader concern of sustainability issues. The topics covered in this issues are: transparent conductive oxides, ceramic composites for tool applications, oxides nanoparticles for A-TIG welding, critical raw materials saving, metallurgical waste treatment, oxides for high temperature applications, nanostructured oxides and composites for gas sensing and desulfuration, and metal oxides sorbents for CO2 capture.